2014
DOI: 10.1007/s13246-014-0308-3
|View full text |Cite
|
Sign up to set email alerts
|

EEG based brain source localization comparison of sLORETA and eLORETA

Abstract: Human brain generates electromagnetic signals during certain activation inside the brain. The localization of the active sources which are responsible for such activation is termed as brain source localization. This process of source estimation with the help of EEG which is also known as EEG inverse problem is helpful to understand physiological, pathological, mental, functional abnormalities and cognitive behaviour of the brain. This understanding leads for the specification for diagnoses of various brain dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 17 publications
1
90
0
1
Order By: Relevance
“…In the current implementation, the solution space consists of 6,239 voxels in the cortical grey matter at 5 mm spatial resolution, using a realistic head model [50] with the MNI152 template [51]. eLORETA has been widely used to explore cortical electrical activities, and its validity has been proved in healthy subjects and neuropsychiatric patients [19-21, 52, 53]. Pascual-Marqui et al [23] also showed the property of correct localization of eLORETA with human EEG data during various sensory stimulations even in the presence of structured noise.…”
Section: Methodsmentioning
confidence: 99%
“…In the current implementation, the solution space consists of 6,239 voxels in the cortical grey matter at 5 mm spatial resolution, using a realistic head model [50] with the MNI152 template [51]. eLORETA has been widely used to explore cortical electrical activities, and its validity has been proved in healthy subjects and neuropsychiatric patients [19-21, 52, 53]. Pascual-Marqui et al [23] also showed the property of correct localization of eLORETA with human EEG data during various sensory stimulations even in the presence of structured noise.…”
Section: Methodsmentioning
confidence: 99%
“…The method used here to estimate the cortical activity was similar to the procedure adopted in (Langer et al, 2013), however, we have employed a source localization technique (eLORETA) that produces more robust and accurate result (Pascual-Marqui et al, 2011; Jatoi et al, 2014) than the approach adopted in (Langer et al, 2013; sLORETA: standardized Low Resolution Electromagnetic Tomography). Specifically, for each EEG data epoch, the power spectrum of each EEG channel and the cross-coherence between all pairs of EEG channels in both frequency bands were obtained with the multi-taper approach using a Hanning window.…”
Section: Methodsmentioning
confidence: 99%
“…LORETA has been applied in almost thousand peerreview publication (Thatcher et al 2012) and has received considerable cross-modal validation from several studies combining LORETA with more established localizing methods such as functional MRI (Vitacco et al 2002;Mulert et al 2004;Mulert et al 2005;Olbrich et al 2009;Neuner et al 2014), structural MRI (Worrell et al 2000;Babiloni et al 2011;Babiloni et al 2013;Vecchio et al, 2015), diffusion spectrum magnetic resonance imaging (Thatcher et al 2012), or positron emission tomography (Pizzagalli et al 2004;Horacek et al 2007). We apply eLORETA, which has no localization bias even in the presence of structured noise ) and, therefore, was found to have a slightly increase localization performance compared to the previous version, called sLORETA (Jatoi et al 2014).…”
Section: Current Source Density Of Neuronal Oscillationsmentioning
confidence: 99%